Rock Grouting at Dam Sites - Ewert, Friedrich-Karl (Professional Practice in Earth Sciences, 2018)
This book focuses on the permeability of the foundation of dams, how to determine their state and how to tighten permeable rock to achieve safe foundations for large dams. It includes theoretical fundamentals as well as lessons learned in their application in practical construction work in eminent projects. It also discusses aspects such as the permeability of the rock mass at the dam site, including the hydraulic characteristics of water conducting openings and their effect on the reliability of water pressure test (WPT) results; the influence of particular geological factors on the hydrogeological regime at the site, as well as the hydrofracturing behavior and individual groutability; and the relationship between quantities of grout takes and the degree of impermeabilization.